Pengaruh kepemimpinan, remunerasi dan mutasi terhadap kinerja pegawai - Zuli Rasyid (Jurnal Kajian Manajemen dan Wirausaha, 2022)
Nowadays, every governments organizational are supposed to increase their job performance, that use to give excellent service to the custumer/society. In order to achieve goal needed qualified human resources.The research was conduct at the Agam Imigrastion Office. The purpose of this research was to determine the effects of leadership, mutation, and remuneration on employee performance, by distributing qustionare for all 42 civil servants and conduct interviews and observations. Then the data is processed used quantitative analysis methods by using SEM (structural equation models) analysis technique based on Smart PLS variance.   The result showed that leadership has positive effect on job performance, The remuneration has positif effect to job performance and mutation has positif effect to job permance.Keywords : leadership; remuneration; mutation; job performance